Inositol transporters AtINT2 and AtINT4 regulate arsenic accumulation in Arabidopsis seeds - Duan, Gui-Lan; Hu, Ying; Schneider, Sabine; Mcdermott, Joseph; Chen, Jian; Sauer, Norbert; Rosen, Barry P.; Daus, Birgit; Liu, Zijuan; Zhu, Yong-Guan (Nature Plants, 2015)
Arsenic contamination of groundwater and soils threatens the health of tens of millions of people worldwide. Understanding the way in which arsenic is taken up by crops such as rice, which serve as a significant source of arsenic in the human diet, is therefore important. Membrane transport proteins that catalyse arsenic uptake by roots, and translocation through the xylem to shoots, have been characterized in a number of plants, including rice. The transporters responsible for loading arsenic from the xylem into the phloem and on into the seeds, however, are yet to be identified. Here, we show that transporters responsible for inositol uptake in the phloem in Arabidopsis also transport arsenic. Transformation of Saccharomyces cerevisiae with AtINT2 or AtINT4 led to increased arsenic accumulation and increased sensitivity to arsenite. Expression of AtINT2 in Xenopus laevis oocytes also induced arsenite import. Disruption of AtINT2 or AtINT4 in Arabidopsis thaliana led to a reduction in phloem, silique and seed arsenic concentrations in plants fed with arsenite through the roots, relative to wild-type plants. These plants also exhibited a large drop in silique and seed arsenic concentrations when fed with arsenite through the leaves. We conclude that in Arabidopsis, inositol transporters are responsible for arsenite loading into the phloem, the key source of arsenic in seeds.